2021
DOI: 10.3389/fphys.2021.592229
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Properties of Subsidiary Atrial Pacemakers in a Goat Model of Sinus Node Disease

Abstract: BackgroundThe sinoatrial/sinus node (SAN) is the primary pacemaker of the heart. In humans, SAN is surrounded by the paranodal area (PNA). Although the PNA function remains debated, it is thought to act as a subsidiary atrial pacemaker (SAP) tissue and become the dominant pacemaker in the setting of sinus node disease (SND). Large animal models of SND allow characterization of SAP, which might be a target for novel treatment strategies for SAN diseases.MethodsA goat model of SND was developed (n = 10) by epica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Studies of experimental animals, using immunohistohemical techniques, have demonstrated the presence of a paranodal area within the terminal crest 25. More recent studies have confirmed the significance of this area in the goat 26. In the serially sectioned histological datasets at our disposal from human hearts, we are able to distinguish the paranodal area using the criteria of Aschoff and Mönckeberg in around one-third of cases.…”
Section: The Criteria For Recognition Of the Components Of The Conduc...mentioning
confidence: 70%
“…Studies of experimental animals, using immunohistohemical techniques, have demonstrated the presence of a paranodal area within the terminal crest 25. More recent studies have confirmed the significance of this area in the goat 26. In the serially sectioned histological datasets at our disposal from human hearts, we are able to distinguish the paranodal area using the criteria of Aschoff and Mönckeberg in around one-third of cases.…”
Section: The Criteria For Recognition Of the Components Of The Conduc...mentioning
confidence: 70%
“…This difference in the architecture of the microvasculature is also paralleled by the differential anatomy of autonomic inputs. 14 There is evidence that in humans 15–17 and goats, 18 the SAN is surrounded by an extensive paranodal area with properties of both nodal and atrial tissues. This paranodal area has been proposed to adopt a role in pacemaking, which could explain the widespread distribution of the leading pacemaker site (wandering pacemaker) in the human right atrium as observed in clinics.…”
mentioning
confidence: 99%